2016
DOI: 10.1080/19440049.2016.1147986
|View full text |Cite
|
Sign up to set email alerts
|

Method development and survey of Sudan I–IV in palm oil and chilli spices in the Washington, DC, area

Abstract: Sudan I, II, III and IV dyes are banned for use as food colorants in the United States and European Union because they are toxic and carcinogenic. These dyes have been illegally used as food additives in products such as chilli spices and palm oil to enhance their red colour. From 2003 to 2005, the European Union made a series of decisions requiring chilli spices and palm oil imported to the European Union to contain analytical reports declaring them free of Sudan I–IV. In order for the USFDA to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
1
15
2
Order By: Relevance
“…(2011) reported a recovery between 85.6 -119.7% in similar study where SPE extraction coupled with direct time-of-flight mass spectrometry were employed. Better recoveries were achieved in this study than that reported by Genualdi et al. (2016) , where recoveries as low as 66.0% were obtained in some cases ( Table 5 ).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…(2011) reported a recovery between 85.6 -119.7% in similar study where SPE extraction coupled with direct time-of-flight mass spectrometry were employed. Better recoveries were achieved in this study than that reported by Genualdi et al. (2016) , where recoveries as low as 66.0% were obtained in some cases ( Table 5 ).…”
Section: Resultscontrasting
confidence: 53%
“…Sudan dyes are synthetic organic dyes (azo dyes) used industrially to colour textiles, plastics, shoe leather and other synthetic products such as floor polish. They are cheap, highly lipophilic and have attractive intense red colours, hence have illegally been used in some food industry as food additives to enhance the colour of foods such as palm oil, spices, powder Chilli pepper and sauces as well as some meat products ( Limin et al., 2007 ; Chailapakula et al., 2008 ; Qi et al., 2011 ; Genualdi et al., 2016 ; Zhang et al., 2016 ; Yang et al., 2019 ). The most commonly used and investigated compound in foods, especially Chilli pepper, among these azo dyes are Sudan I, II, III, and IV ( Zheng et al., 2007 ; Ávila et al., 2011 ; Qi et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to detect dye elution, a UV-Vis detector was selected and used at a wavelength of 460 nm, which is in the absorption range of this compound. Some attempts to find an alternative to this compound have been previous carried out as it is known to be both toxic and carcinogenic, and its addition to food as a colorant is not permitted (Genualdi et al, 2016) [ 31 ]. In particular, α-tocopherol and bixin were tested, but satisfactory results were not obtained, due to different retention times and low solubility in the solvent used for the analysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this and the serious health risks associated with this toxic chemical, there are only a few published methods for detecting Sudan dyes I-IV in palm oils. For example, it is reported that the relatively old and imprecise method of qualitative thin layer chromatography (TLC) is still used by the UK Food Standards Agency to detect Sudan dyes in food products (Oco and Egroodt, 2006;Genualdi et al, 2016). A similar but more advanced method involving diode array detection (DAD), conversion of the oil to FA methyl esters and further purification by silica gel chromatography has also been used successfully (Uematsu et al, 2007).…”
Section: Sudan Adulteration In Palm Oilsmentioning
confidence: 99%
“…A recent study by Genualdi et al (2016) assessed the use of LC-diode array detection (DAD) analysis and LS-MS/MS, for the extraction and detection of Sudan dyes I-IV in palm oil and chilli spices. The study examined both methods for their strengths and weaknesses in identifying adulterated samples.…”
Section: Sudan Adulteration In Palm Oilsmentioning
confidence: 99%